식품전용 산업단지 조성사업 타당성조사 및 기본구상 - 최지현 (한국농촌경제연구원, 2009)
The purpose of this study is to analyze the feasibility of establishing Food Cluster Korea, make the plan, survey 1,021 food companies and research institutes to identify their understanding of the cluster, and find a basic spatial structure. The cluster will be located in the city of Iksan, Jeollabukdo with an investment of 1 trillion won till 2015. The central government will be providing facility support for the cluster, such as food R&D centers, food processing facilities, joint collection and distribution facilities, and venture incubation centers. The food cluster will be assisting various organizations including the local food industry, overseas food industry clusters, universities, and research institutes, providing administrative and financial support for network improvement and R&D, and other activities aimed at increasing exports. The concept of the cluster is 1) to pursue synergy through close networks among food industries, academies, and institutes, 2) to create sustainable values by adopting various functions of industries including accommodation, commerce, manufacturing, and agriculture, and 3) to present a next-generation industry that is built harmoniously with traditional culture. The survey revealed that over a half of 225 companies, or 57.3% of the surveyed, already knew about the cluster. Most of them got the information about the cluster from the news media such as newspapers, TV, and radio. Forty three percent of the surveyed companies have willingness to participate in the food cluster. The results of the feasibility analysis show that the Benefit/Cost(BC) ratio ranges from 0.5 to 4.3, and the Internal Rate of Return(IRR) is from 0.2% to 30.4%. Therefore, it indicates that Food Cluster Korea may have economical efficiency if the headquarters of the cluster attracts over 50 companies with over 50 employees per company.